Performance of Resource Management Techniques for Weather-Impacted Satellite Networks. (1st December 2019) - Imole, Olugbenga Emmanuel; Walingo, Tom Mmbasu
Abstract : Signals transmitted via satellite networks at high frequency in the Ka, Q, and V bands are susceptible to degradation due to rain attenuation. Adaptive transmission techniques are usually employed to mitigate the effect of rain and improve users' quality of service (QoS) but the effectiveness of these techniques hinges on the accuracy with which rain attenuation on the link is known. Commonly, most techniques rely on predicted attenuation along the link for selection of optimal transmission parameters. This paper proposes an efficient approach to predict the rain attenuation experienced by sources of multimedia connections in rain-impacted satellite networks. The proposed technique is based on three Markov models for widespread, shower, and thunderstorm rain events and predicts the attenuation experienced at different periods within the duration of a user's connection. It relies on an adaptive modulation and coding (AMC) scheme to dynamically mitigate rain attenuation and a call admission control (CAC) policy to guarantee the satisfaction of users' QoS requirements.